Pre-Service EFL Teachers' Responses to a Systemic Functional Linguistics Pedagogical Unit : An Experience in a Public University in Colombia (2021)
ABSTRACT: Acknowledging the need for pre-service teachers to learn about language struc-tures, many teacher preparation programs have incorporated grammar courses into their curriculum. Recently, there has been a push from Systemic Functional Linguistic (sfl) scholars to switch to more functional views of grammar in these courses. Such a switch, scholars claim, can better prepare pre-service teachers (pst) for writing across the curriculum and for teaching writing to their prospective stu-dents. Despite the potential benefits, many efl teacher preparation programs are still cautious about providing instruction on sfl. This has created a gap in terms of how pre-service teachers would respond to this type of instruction. Consid-ering this gap, scholars from a university in Medellín, Colombia implemented a three-month pedagogical unit within a grammar course, which intended to move pre-service teachers from traditional to functional views of grammar. As they did this, they conducted a case study which explored how psts responded to the implementation of this unit. Data analysis shows that psts’ responses do not al-ways move in a straight line, that is, from resistance, to caution, to openness, but may very well vary depending on the sfl concept or premise that is being taught. The results suggest that English grammar courses offered in teacher preparation programs can have traditional grammar as a starting point and then move psts towards more functional and critical views. They also suggest the need to identify some strategies that could be used with psts who show either caution or resistance.